Предмет: Алгебра,
автор: arianalayne13
(5c - 6) (5c + 6) - (5c - 6)² при c = 13
Ответы
Автор ответа:
9
(5c - 6)(5c + 6) - (5c - 6)² = 25c² - 36 - (25c² - 60c + 36) =
= 25c² - 36 - 25c² + 60c - 36 = 60c - 72
если c = 13 , то : 60 * 13 - 72 = 780 - 72 = 708
arianalayne13:
Спасибо!!
Похожие вопросы
Предмет: Українська мова,
автор: nastyakorol2009
Предмет: История,
автор: stas7577
Предмет: Физкультура и спорт,
автор: hwhsywhjwhw
Предмет: Математика,
автор: lemanamiraslan
Предмет: Алгебра,
автор: Anastasia2134